KALENDER ROWOT SASAK - Awaludin, Muhammad; Sado, Arino Bemi; Muhammad Haikal Rivaldi (UIN ALAUDDIN MAKASSAR, 2023)
Indonesia, has two calendars that have been strongly attached to the way of life in its society. These are the Gregorian calendar and the Hijri calendar. In addition, each region of Indonesia also has its own traditional calendar system. One type of traditional calendar that is still alive today is the Rowot Sasak Calendar. The Rowot Sasak Calendar uses the Moon as the base for its calculation system, so it is very similar to the Hijriyah system. But as a traditional calendar, the cultural components in it are very similar to the Islamic Javanese Calendar. So the author is interested in further research on the existence of cultural acculturation between Islam, Java and Sasak in the Rowot Sasak Calendar. This research uses qualitative methodology with field study research type and descriptive qualitative analysis. The findings of this study indicate that there is a strong acculturation between the three cultures in the rowot sasak calendar. The acculturation is based on the system that uses the Islamic calendar (Hijriyah) urfi hisab system. This is proven by the names of the months that adopt from the Hijriyah calendar, as well as the number of days 29/30 each month. Meanwhile, the Javanese cultural element can be identified in the component of determining good days for the community. In addition, the use of market names such as kliwon, wage, pahing, pon and legi is strong evidence of Javanese cultural acculturation. While the elements of Sasak culture itself can be found in the mention of the name of the day and other cultural terms that use terms in the Sasak language. As well as the determination of mangse (season) which uses the 5-15-25 tradition benchmark with synchronization on the Hijriyah calendar.